Transmission of trypanosoma species and the host role of proechimys semispinosus in Panama - Snyder, Ehren (My University, 2017)
Parasites, particularly those that utilize a vector, play an important role throughout tropical forests. Their prevalence and distribution depend on the distribution of their vectors. Wherever these vectors are found, there also has to be a suitable host for the parasite to persist in the environment. Due to their abundance, diversity, and ubiquity throughout tropical forest, rodents present an ideal host group for scientific inquiry. The Central American spiny rat, Proechimys semispinosus, has been the target of many such studies because of its abundance in disturbed forest, susceptibility to infection, and ease of sampling. Previous studies have documented its endo- and ectoparasites, some of which infect humans. One such parasite is Trypanosoma cruzi (causal agent of Chagas’ disease). It has been identified infecting P. semispinosus in Central Panama, but preliminary findings indicate another trypanosome also may be present. My study sought evidence to identify the trypanosomes that were infecting P. semispinosus in Central Panama, the putative vector, and the potential role of the spiny rat as a host. Trypanosoma lewisi and T. renjifoi, parasites closely related to T. cruzi, have been described infecting various Proechimys species in Central and South America but have never been found in Panama. Recent studies have identified a parasite similar to T. lewisi infecting P. semispinosus, but its transmission cycle is largely unknown. I studied how this trypanosome persists in the environment and the conditions that promote its transmission. Proechimys semispinosus was sampled by live-trapping in degraded forest fragments in Central Panama. A blood sample, two blood smears, and fleas (if present) were collected from each captured individual. Blood samples were used for molecular tests, blood smears for light microscopic scans, and fleas for T. renjifoi infection. I hypothesized that T. renjifoi would be present in degraded forests near people, that P. semispinosus would be a competent reservoir, and that fleas would be the vector. Preliminary results showed that all 14 captured rats were negative for both trypanosome infection and flea infestation during the first sampling season. The second season resulted in 13 total captures of rats, of which 6 were infested with fleas. One collected flea from the rats was infected with a trypanosome (presumably T. renjifoi). However, more flea sampling needs to be conducted to further understand conditions that promote transmission. This study provides a model for how a vector-borne parasite can be described and as a basis for further studies of the transmission of T. renjifoi. It also begins to describe one of the many factors that may affect T. cruzi in its natural environment. Understanding the entirety of this ecosystem is necessary prior to implementation of disease control methods and for conservation purposes.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science of Biology